If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -2 = -7 Reorder the terms: -2 + a = -7 Solving -2 + a = -7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + a = -7 + 2 Combine like terms: -2 + 2 = 0 0 + a = -7 + 2 a = -7 + 2 Combine like terms: -7 + 2 = -5 a = -5 Simplifying a = -5
| y-15=31 | | 6+x=20 | | 1.2(3g-2)=g.6 | | 3x*2+5x=2 | | 2-3.4z=1.8z+9 | | (2y^2-7y-1)+(4y^2-5y+3)= | | 11y-9=35 | | 15x^2+5=0 | | 13-0.75x=-8 | | 2/2= | | 3(6x+8)-5(2x+3)= | | 10(x+3)-(-9x-4)=x-5+30 | | 2.3x-1.6=1.2x+5.6 | | 7a=12+4a | | 186-4x=41x+21 | | 0.5(5x-7)+3=11 | | -45-8x=113-29x | | 10x^2+45x+35= | | -6(8-b)-20=5b | | 3t+14=5t+12 | | 3x^2+30x=0 | | 2+10-3=6 | | -10=-4-2x | | 4x+5=2(x+7) | | 4(n-3)-12=-n | | -3x-6=12 | | 12(v+4)-4v=2(4v+3)-15 | | x^3*5=625 | | -x/2= | | 4j-2=3j | | 2*(x-4)+3=5x-1 | | 18*3x=6 |